(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Interaction of levomicytine anion with okcin raw pironine «B» has been studied. Compound forming in the system is extracted by dichloretane–carbon tetrachloride (7+3 mL) binary mixture. Maximal light absorbanse (extinction) for extracts forming compound as well as for «blind» extracts is observed at 535 nm wavelength. At the optimal acidity conditions (pH 5.8 by HCl) levomicytine is extracted almost quantitatively (R=95%) to the organic solvent phase by means of single extraction during 1 minutes shaking. The range of determined concentration of levomicytine is 12.5–175 mkg/10 mL. The molar coefficient of extinction is ε535 = 5.07·104 L·mol–1·cm–1 The method was used for determination of small amounts of levomicytine.